Literature Review on the Relationship between Total Productive Maintenance (TPM), Lean Maintenance, and Healthcare Systems’ Sustainable Performances - Taufik, Taufik; Kamil, Insannul; Hasan, Alizar; Afrinaldi, Feri (Department of Mechanical Engineering, Universitas Andalas, 2025)
This paper explores theoretical and practical foundations for integrating Total Productive Maintenance (TPM) and lean maintenance to achieve healthcare systems' sustainable performances. A systematic literature review is performed. The review methodology consists of seven steps: defining the research question, searching the literature, screening the literature, documenting the search results, assessing articles' quality, documenting the review results, and synthesizing. The search found a limited number of publications exploring the relationship between TPM and lean maintenance to achieve sustainable performances of healthcare systems. Most contributors were from developing countries. The publication peaked in 2023 and 2024, and the number tended to rise from 2012 to 2024. The synthesis process shows limited evidence about the relationship between TPM and hospital sustainable performance. Theoretically, the relationship between TPM, lean maintenance, and sustainable performance in healthcare systems is plausible. However, the concepts were rarely tested. For future research, this paper proposes to investigate the relationship between TPM practices and hospitals' sustainable performance moderated by lean maintenance. A conceptual model is also presented.